2020
DOI: 10.1021/acs.jnatprod.0c00963
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Screening of Xanthones from Garcinia oligantha Identified Oliganthin H as a Novel Natural Inhibitor of Convulsions

Abstract: Epilepsy is a chronic neurological disorder, characterized by recurrent, spontaneous, and transient seizures, and affects more than 70 million people worldwide. Although two dozen antiepileptic drugs (AEDs) are approved and available in the market, seizures remain poorly controlled in one-third of epileptic patients who are suffering from drug resistance or various adverse effects. Recently, the xanthone skeleton has been regarded as an attractive scaffold for the discovery and development of emerging anticonv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 83 publications
(176 reference statements)
0
13
0
Order By: Relevance
“…GABA-mediated neurotransmission starts at the early stage of fish development, which begins after the patterning of the spinal cord and hindbrain, regulating the circuitry underlying locomotor behaviors (e.g., rhythmic swimming response) [ 50 ]. Gad1b encodes glutamic acid decarboxylase, converting glutamate into GABA [ 51 ]. Abat encodes the key rate-limiting enzyme for GABA degradation [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GABA-mediated neurotransmission starts at the early stage of fish development, which begins after the patterning of the spinal cord and hindbrain, regulating the circuitry underlying locomotor behaviors (e.g., rhythmic swimming response) [ 50 ]. Gad1b encodes glutamic acid decarboxylase, converting glutamate into GABA [ 51 ]. Abat encodes the key rate-limiting enzyme for GABA degradation [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…No significant alteration of glsa expression was observed, indicating that THCP may not affect the synthesis of the raw material of GABA. GABA A receptor (encoded by gabra1 ) is universally found in mature neurons, taking part in mediating majority of fast inhibitory transmission [ 51 ]. It was reported that the up-regulation of gabra1 can suppress stress- or anxiety-related behavior of zebrafish [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compounds with antiseizure activity diminish PTZ-induced hyperlocomotion and decrease the number of LFP based epileptiform-discharges [ 7 , 14 ]. Using this model, the antiseizure activity of various plant-derived constituents have been identified, e.g., oliganthin H from Garcinia oligantha [ 15 ], palmatine from Berberis sibirica [ 13 ], indirubin from Indigofera arrecta [ 16 ], or bisabolene sesquiterpenoids from Curcuma longa [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, ,, cytotoxicity is one of the most frequently reported biological effects of xanthones, with cancer being a severe and enormous threat to human health. Thus, these isolates were subjected to cytotoxic evaluation using an MTT assay.…”
Section: Results and Discussionmentioning
confidence: 99%